Encyclopedia of caves - White, William B. (William Blaine), 1934-; Culver, David C., 1944-; Pipan, Tanja (Academic Press, 2019)
Encyclopedia of Caves, Third Edition, provides detailed background information to anyone with a serious interest in caves. This includes students, both undergraduate and graduate, in the earth, biological and environmental sciences, and consultants, environmental scientists, land managers and government agency staff whose work requires them to know something about caves and the biota that inhabit them. Caves touch on many scientific interests in geology, climate science, biology, hydrology, archaeology, and paleontology, as well as more popular interests in sport caving and cave exploration. Case studies and descriptions of specific caves selected for their special features and public interest are also included. This book will appeal to these audiences by providing in-depth essays written by expert authors chosen for their expertise in their assigned subject.